An overview of health workforce mobility in the European Union under the current supply challenges. SESPAS Report 2024 - Angela Blanco Moreno (Elsevier, 2024)
Objective: Providing a general overview of the European Union's health workforce mobility under the challenges facing health systems regarding the supply of health workers. Method: We use a descriptive method, based on the analysis of secondary data, qualitative and quantitative, concerning the European Semester from the European Union, complemented with statistical data from both the Union and some international organisations. Results: The mobility of health professionals in the Union, associated to strong reliance on recruiting abroad and shortages due to emigration, was identified as a challenge in the European Semester process in a significant number of times during 2017-2023. The pandemic aggravated pre-existing shortages and the need to strike a balance between maintaining the resolution capacity of health systems while abiding by the free movement of health professionals. The information shows that Romania, Slovakia, Spain, Lithuania, Latvia, Portugal, Bulgaria, Greece, Croatia, Hungary, Italy, and Slovenia could be flagged with an "issuer profile". Luxembourg, Ireland, Malta, and Sweden could be flagged with a "recipient profile". We benefited from improvements in the information system concerning the Union's health workforce. Further advances regarding the harmonisation of health professions' definition are needed, especially for nurses. Conclusions: The European Union faces internal migrations of health professionals. Mobility is used as a solution to shortages. The pandemic aggravated pre-existing shortages bringing to the forefront the need to strike a balance between health objectives and internal market objectives. Member States are immersed in health reforms, some financed with European Funds. Promoting health workforce planning and forecasting would emerge as a necessary action, including improving harmonised information. Drawing in a systematic way on the available information from the European Semester reports may provide some clues to give answers to policymaking concerning health professionals' mobility. Resumen: Objetivo: Proporcionar una visión general de la movilidad del personal sanitario de la Unión Europea ante los desafíos a los que se enfrentan los sistemas sanitarios relacionados con la oferta de profesionales. Método: Utilizamos un método de investigación descriptivo, basado en el análisis de información secundaria, cualitativa y cuantitativa, relativa al Semestre Europeo de la Unión Europea, complementada con datos estadísticos tanto de la Unión Europea como de algunas organizaciones internacionales. Resultados: La movilidad de los profesionales sanitarios en la Unión Europea, asociada a problemas de fuerte dependencia de la contratación de profesionales extranjeros y escasez debido a la emigración, se identificó como un desafío en el proceso del Semestre Europeo en un número significativo de veces durante el periodo 2017-2023. La pandemia agravó la escasez preexistente, enfatizando la necesidad de lograr un equilibrio entre mantener la capacidad resolutiva de los sistemas sanitarios y respetar al mismo tiempo la libre circulación de los profesionales sanitarios. La información muestra que Rumanía, Eslovaquia, España, Lituania, Letonia, Portugal, Bulgaria, Grecia, Croacia, Hungría, Italia y Eslovenia se podría considerar que tienen un «perfil emisor». Luxemburgo, Irlanda, Malta y Suecia tendrían un «perfil receptor». Algunas mejoras registradas en el sistema de información sobre recursos humanos en el sector sanitario de la Unión Europea han resultado útiles. Sería preciso realizar más avances en la armonización de la definición de profesiones sanitarias, especialmente para la enfermería. Conclusiones: La Unión Europea se enfrenta a migraciones internas de profesionales sanitarios. La movilidad se utiliza como solución a la escasez. Parece que la pandemia agravó la escasez preexistente, poniendo en primer plano la necesidad de las autoridades sanitarias de lograr un equilibrio entre los objetivos sanitarios y los objetivos del mercado interior. Los Estados miembros están inmersos en reformas sanitarias, algunas financiadas con Fondos Europeos. Promover la planificación y la previsión del personal sanitario sería una acción necesaria, incluida la mejora de la información armonizada. Además, extraer de forma sistemática la información disponible de los informes del Semestre Europeo proporcionaría claves para dar respuestas a la formulación de políticas sobre movilidad de los profesionales sanitarios.